Productivity dynamics of agroecosystems under prevailing and alternative management practices across the United States - Omodara E. Obisesan; Adam P. Schreiner-McGraw; Jeffrey D. Wood; Jiquan Chen; Joshua D. Gamble; Timothy J. Griffis; Christina M. Helseth; Makki Khorchani; Claire L. Phillips; Kathryne Rumora; Russell L. Scott; Xiangmin Sun; et al. (Agricultural and Forest Meteorology, 2026)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Observed CO2 concentration reveals steep decrease of anthropogenic emissions in winters of 2021 and 2022 in Hangzhou and Yangtze River Delta region, China - Cheng Hu; Huili Liu; Yifan Zhang; Yu Cui; Fan Sun; Xuejing Shi; Junqing Zhang; Yanrong Yang; Leying Zhang; Bing Qi; Qitao Xiao; Ning Hu; et al. (Science of The Total Environment, 2025)

Combining stable isotopes and spatial stream network modelling to disentangle the roles of hydrological and biogeochemical processes on riverine nitrogen dynamics - Minpeng Hu; Zhongjie Yu; Timothy J. Griffis; John M. Baker (Water Research, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

Multiple-model based simulation of urban atmospheric methane concentration and the attributions to its seasonal variations: A case study in Hangzhou megacity, China - Junqing Zhang; Dan Ji; Cheng Hu; Timothy J. Griffis; Qitao Xiao; Xinyue Ai; Huili Liu; Xuejing Shi; Fan Sun; Bing Qi; Wei Xiao (Environmental Pollution, 2024)

Efficacy of grape seed procyanidins for inhibiting denitrification varies by source, soil texture, and cropping history - Che-Jen Hsiao; Alexander Frie; Scott Mitchell; Rodney Venterea; Timothy Griffis (Applied Soil Ecology, 2024)

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

A coupled equilibrium boundary layer model with stable water isotopes and its application to local water recycling - Ke Xiao; Timothy J. Griffis; Xuhui Lee; Wei Xiao; John M. Baker (Agricultural and Forest Meteorology, 2023)

Corrigendum to ’Distinct driving mechanisms of non-growing season N2O emissions call for spatial-specific mitigation strategies in the US Midwest’ [Agricultural and Forest Meteorology 324 (2022) 109108] - Yufeng Yang; Licheng Liu; Wang Zhou; Kaiyu Guan; Jinyun Tang; Taegon Kim; Robert F. Grant; Bin Peng; Peng Zhu; Ziyi Li; Timothy J. Griffis; Zhenong Jin (Agricultural and Forest Meteorology, 2023)

Evaluation and improvement of the E3SM land model for simulating energy and carbon fluxes in an Amazonian peatland - Fenghui Yuan; Daniel M. Ricciuto; Xiaofeng Xu; Daniel T. Roman; Erik Lilleskov; Jeffrey D. Wood; Hinsby Cadillo-Quiroz; Angela Lafuente; Jhon Rengifo; Randall Kolka; Lizardo Fachin; Craig Wayson; et al. (Agricultural and Forest Meteorology, 2023)

The global biogeography of soil priming effect intensity - Chengjie Ren; Fei Mo; Zhenghu Zhou; Felipe Bastida; Manuel Delgado‐Baquerizo; Jieying Wang; Xinyi Zhang; Yiqi Luo; Timothy J. Griffis; Xinhui Han; Gehong Wei; Jun Wang; et al. (Global Ecology and Biogeography, 2022)
Aim Fresh carbon (C) inputs to the soil can have important consequences for the decomposition rates of soil organic matter (priming effect), thereby impacting the delicate global C balance at the soil–atmosphere interface. Yet, the environmental factors that control soil priming effect intensity remain poorly understood at a global scale. Location Global. Time period 1980–2020. Major taxa studied Soil priming effect intensity. Methods We conducted a global dataset of CO 2 effluxes in 711 pairwise soils with 13 C or 14 C simple C sources inputs and without C inputs from incubation experiments in which isotope‐labelled C was used to quantify fresh C‐induced rather than exudate‐induced priming. Results Soil priming effect intensity is predominantly positive. Soil texture and C content were identified as the most important factors associated with priming effects, with sandy soils from tropical and mid‐latitudes supporting the highest soil priming effect intensity, and soils with greater C content and fine textures from high latitudes maintaining the lowest soil priming effects. The negative association between C content and soil priming effect intensity was also indirectly driven by changing mean annual temperature, net primary productivity, and fungi : bacteria ratio. Using this information, we generated a global map of soil priming effect intensity, and found that the priming was lower at high latitudes and higher at lower latitudes. Main conclusions Global patterns of soil priming effect intensity can be predicted using environmental data, with soil texture and C content playing a predominant role in explaining in priming effects. These effects were also indirectly driven by climate, vegetation and soil microbial properties. We present the first global atlas of soil priming effect intensity and advance our knowledge on the potential mechanisms underlying soil priming effect intensity, which are integral to improving the climate change and soil C dynamics components of Earth System models.

Seasonal Variations of CH4 Emissions in the Yangtze River Delta Region of China Are Driven by Agricultural Activities - Wenjing Huang; Timothy J. Griffis; Cheng Hu; Wei Xiao; Xuhui Lee (Advances in Atmospheric Sciences, 2021)

Quantifying nitrous oxide fluxes on multiple spatial scales in the Upper Midwest, USA - Xin Zhang; Xuhui Lee; Timothy J. Griffis; Arlyn E. Andrews; John M. Baker; Matt D. Erickson; Ning Hu; Wei Xiao (International Journal of Biometeorology, 2015)

The influence of plants on atmospheric methane in an agriculture-dominated landscape - Xin Zhang; Xuhui Lee; Timothy J. Griffis; John M. Baker; Matt D. Erickson; Ning Hu; Wei Xiao (International Journal of Biometeorology, 2014)

Mosquitoes of North America with emphasis in the midwestern United States: long‐term occurrence patterns - Jessica J. Hellmann; Jason D. K. Dzurisin; Timothy Wright; David Cieslak; Samuel Pecoraro; Kaitlyn E. Smith; Katharine Hayhoe; Kerry L. Griffis-Kyle (Ecology, 2013)
Mosquitoes are ecologically and economically important invertebrates that transmit numerous diseases and are an integral part of the food web in many terrestrial and aquatic ecosystems. Despite their importance, there have been no central repositories for occurrence or abundance records of mosquitoes in the United States. To enable research dependent on the geographic distribution and abundance of mosquito species, we built a database of occurrence records collected by many individuals and agencies, primarily in the United States and with emphasis on unpublished data in the Midwest region. This resource is invaluable to researchers studying mosquito ecology, disease vectors and pathways, and insect pests. The database contains 542 144 occurrence records, and each record includes information on sex, life stage, sampling method, presence/absence or abundance, and date and location of sampling. The accessibility of this resource will directly impact management and planning for mosquito‐borne diseases with region‐specific or species‐specific modeling. Because there is little centralized ecological information on mosquitoes, this database is foundational to expanding knowledge of mosquito ecology.

Modelling the interannual variability of net ecosystem CO 2 exchange at a subarctic sedge fen - Timothy J. Griffis; Wayne R. Rouse (Global Change Biology, 2001)
This paper presents an empirical model of net ecosystem CO 2 exchange (NEE) developed for a subarctic fen near Churchill, Manitoba. The model with observed data helps explain the interannual variability in growing season NEE. Five years of tower‐flux data are used to test and examine the seasonal behaviour of the model simulations. Processes controlling the observed interannual variability of CO 2 exchange at the fen are examined by exploring the sensitivity of the model to changes in air temperature, precipitation and leaf area index. Results indicate that the sensitivity of NEE to changing environmental controls is complex and varies interannually depending on the initial conditions of the wetland. Changes in air temperature and the timing of precipitation events have a strong influence on NEE, which is largely manifest in gross ecosystem photosynthesis (GEP). Climate change scenarios indicate that warmer air temperatures will increase carbon acquisition during wet years but may act to reduce wetland carbon storage in years that experience a large water deficit early in the growing season. Model simulations for this subarctic sedge fen indicate that carbon acquisition is greatest during wet and warm conditions. This suggests therefore that carbon accumulation was greatest at this subarctic fen during its early developmental stages when hydroclimatic conditions were relatively wet and warm at approximately 2500 years before present.

Scaling net ecosystem CO 2 exchange from the community to landscape‐level at a subarctic fen - Timothy J. Griffis; Wayne R. Rouse; J. M. Waddington (Global Change Biology, 2000)
Summary Landscape‐ and community‐level CO 2 measurements were made at a subarctic sedge fen near Churchill Manitoba during the 1997 growing season. Climatic conditions were warmer and drier than the 30‐y normal. Landscape‐scale micrometeorological measurements indicated that the wetland gained 49 g CO 2 m −2 during the growing season. Chamber‐scale measurements from the main vegetation community types showed that small hummocks ( Carex spp. sites) dominated the CO 2 exchange, yielding an effective scaling factor of 70%. Scaled parameters of two algorithms describing photosynthesis and respiration for each community type show strong similarity to those derived at the landscape level. Scaling photosynthesis, respiration, and net ecosystem CO 2 exchange from the community to landscape‐level over the season is within the maximum probable error of each methodological approach and helps substantiate the 1997 CO 2 budget. We explore the equilibrium response of net ecosystem CO 2 exchange of this fen to climatic change by examining the feedback of water table position on vegetation distribution and nitrogen availability. Based on the effective scaling factors computed for each community type, we hypothesize that a small decrease in mean water table position could nearly triple the net uptake of CO 2 at this wetland.